Immunization against Mpox infection is coercive: A timely call - Ahmed, Iftekhar; Ahamed, Rayhan; Bari, Lazima Faiah; Shanto, Md. Yusuf; Tahsin, Md. Rafat (Bangladesh Journal of Infectious Diseases, 2025)
Mpox or monkeypox is a viral zoonotic disease caused by the monkeypox virus (MPXV). Recently, Mpox has been on the rise, and its multi-country spread has alarmed health officials throughout the world. Vaccination is essential for the prevention and management of mpox cases because there is currently no particular cure against the mpox virus. The current mpox epidemic calls for urgent action in the form of immunization. However, the smallpox vaccine and a newer vaccine named Modified Vaccinia Ankara (MVA) vaccine are effective against the disease. JYNNEOS vaccine is approved to be used in mpox cases. However, its efficacy and wide-scale production are still a matter of concern. The ACAM2000 vaccine, which also protects against both smallpox and mpox though it has severe adverse effects. Only an effective vaccination can drastically lower mpox infection and death rates. Safe and effective vaccines, along with their equitable distribution, are vital for global health. This article explores the importance of addressing this challenge. Bangladesh Journal of Infectious Diseases, June 2025;12(1):185-188